Evolutionary history of the Cameroon radiation of puddle frogs (Phrynobatrachidae: Phrynobatrachus), with descriptions of two critically endangered new species from the northern Cameroon Volcanic Line - Václav Gvoždík; Tadeáš Nečas; Matej Dolinay; Breda M. Zimkus; Andreas Schmitz; Eric B. Fokam (PeerJ, 2020)
The Cameroon Volcanic Line, a mountain chain located between West and Central Africa, is a region of numerous endemic diversifications, including of puddle frogs (Phrynobatrachus). This study reviews the phylogeny and taxonomy of puddle frogs of the “Cameroon radiation,” which is a clade containing mainly montane but also at least three lowland species. Molecular data revealed a novel evolutionary lineage from high altitudes in the northern part of the mountains. Puddle frogs from the new, minute-sized (SVL < 20 mm) lineage are identified using molecular, morphological and acoustic data and described as two new species, Phrynobatrachus arcanus sp. nov. (Gotel Mountains, Cameroon–Nigeria) and P. mbabo sp. nov. (Tchabal Mbabo, Cameroon). The tadpole of the first species is also described. Phylogenetic analyses placed the new lineage to the proximity of the recently described lowland small-sized taxa (P. horsti, P. ruthbeateae). Based on the inferred phylogeny, we propose five species groups within the Cameroon radiation: P. arcanus, P. chukuchuku, P. ruthbeateae, P. steindachneri, and P. werneri. The taxonomically enigmatic P. hylaios is proposed to be a member of the P. ruthbeateae species group. The basal radiation evolved during the late Miocene with subsequent diversifications occurring during the Pliocene, while closely related terminal taxa originated during the Pleistocene. We recommend that the newly described species are categorized as Critically Endangered due to their limited ranges and because recent surveys did not identify any individuals at the type localities. This further supports the need for conservation interventions in the mountains of Cameroon and Nigeria.